KOMPLEKSITAS DAN KEBERAGAMAN SENI MENUNJUKAN SUATU IDENTITAS - Jermias Van Harling (TANGKOLEH PUTAI, 2022)
The discourse of "identity" becomes a crucial issue when it is in the global realm (globalization). The battle begins in various cultural arenas by adopting cultural components as self-image for legitimacy. Not only that, because cultural awareness is also modified, elaborated into various typifications that aim to influence and invite the attention of the outside world. This is the way in which identity becomes something that is contested. The term identity is very attached to certain entities, is interdependence and in contact with local culture, including art as a symbol of self-expression. Art in Indonesia as a cultural component is part of the formation of self-identity, but the fact is that when faced with the domination of Western arts, Indonesian art is increasingly dwarfed, why is that? because art in Indonesia is sometimes drowned in the flow of globalization. The originality of traditional (Indonesian) art is reduced to being packaged in the rules of Western art. This article intends to provide an explanation of how art in Indonesia, in its diversity and complexity, can be seen as a medium for building an ethnic identity that contributes to strengthening national identity.